Does chlorination of seawater reverse osmosis membranes control biofouling? - Khan, M.; Hong, P.; Nada, N.; Croue, Jean-Philippe (Elsevier Ltd, 2015)
Biofouling is the major problem of reverse osmosis (RO) membranes used for desalting seawater (SW). The use of chlorine is a conventional and common practice to control/prevent biofouling. Unlike polyamide RO membranes, cellulose triacetate (CTA) RO membranes display a high chlorine tolerance. Due to this characteristic, CTA membranes are used in most of the RO plants located in the Middle East region where the elevated seawater temperature and water quality promote the risk of membrane biofouling. However, there is no detailed study on the investigation/characterization of CTA-RO membrane fouling. In this investigation, the fouling profile of a full-scale SWRO desalination plant operating with not only continuous chlorination of raw seawater but also intermittent chlorination of CTA-RO membranes was studied. Detailed water quality and membrane fouling analyses were conducted. Profiles of microbiological, inorganic, and organic constituents of analysed fouling layers were extensively discussed. Our results clearly identified biofilm development on these membranes. The incapability of chlorination on preventing biofilm formation on SWRO membranes could be assigned to its failure in effectively reaching throughout the different regions of the permeators. This failure could have occurred due to three main factors: plugging of membrane fibers, chlorine consumption by organics accumulated on the front side fibers, or chlorine adaptation of certain bacterial populations.